Optimization of Dispersible Diclofenac Potassium Tablet Formula with a Combination of Explotab and Avicel PH-101 - Kurniawan, Dhadhang; Andiani, Nauli Marsha; Utami, Vitis Vini Fera Ratna (Clinical and Pharmaceutical Sciences Journal, 2025)
Diclofenac potassium is a nonsteroidal anti-inflammatory drug (NSAID) frequently employed as an analgesic therapy for inflammatory conditions and pain associated with Osteoarthritis and Rheumatoid Arthritis. It is formulated as a dispersible tablet, requiring dispersion in solution prior to administration to expedite onset and facilitate use, particularly for patients with difficulty swallowing intact tablets. This study aims to investigate the effects of the optimal combination and proportion of Explotab and Avicel pH-101 in the formulation of diclofenac potassium dispersible tablets using the Simplex Lattice Design (SLD) method with two factors. The tablet formulations, based on the SLD method with Explotab (A) and Avicel pH-101 (B) as excipients, are as follows: FI (100% A), FII (75% A:25% B), FIII (50% A:50% B), FIV (25% A:75% B), and FV (100% B). The tablets were prepared via direct compression and subsequently evaluated for their physical properties, including hardness, friability, size uniformity, weight uniformity, disintegration time, dispersion time, wetting time, and content determination. The study's findings indicated that the combination of Explotab and Avicel pH-101 affected the physical properties of the tablets, notably decreasing weight uniformity, enhancing tablet hardness, reducing friability, and prolonging both disintegration and dispersion times of the diclofenac potassium dispersible tablets. The optimal formula was identified as comprising 40% Explotab and 60% Avicel pH-101. This optimal formulation was determined based on the highest total response value calculated using the Simplex Lattice Design with two factors